Post-Uruguay Round price linkages between developed and developing countries: the case of rice and wheat markets - Yavapolkul, Navin; Gopinath, Munisamy; Gulati, Ashok (Wiley, 2006)
The Uruguay Round Agreement on agriculture attempted to lower distortions in global agricultural markets. However, the significant fall in commodity prices in the late 1990s may have reduced the incentives for both developed and developing countries to better integrate into world markets. This study analyzes price linkages and adjustment between developed and developing countries during the post–Uruguay Round period. Prices of two key commodities, long-grain rice and medium-hard wheat, are assembled for major exporters and producers. Results of multivariate cointegration analysis suggest partial market integration between developed and developing countries in the post–Uruguay Round period. Developed countries are found to be price leaders in these two markets, and in most cases, changes in their prices have relatively large impacts on those of the developing countries. Developing countries (e.g., Vietnam and Argentina) have faced considerable price adjustment due to changes in the developed countries' prices.